How repeated studying and testing affects multimedia learning: Evidence for adaptation to task demands. (February 2016) - Eitel, Alexander
Abstract: Two biases can occur in multimedia learning: overconfidence and over-reliance on text processing. The present research sought to identify these biases and to investigate whether they can be reduced, and hence learning fostered, when studying and testing are repeated. In 2 experiments (Exp.1: N  = 79, Exp.2: N  = 52), students learned either with text only or with text and pictures (multimedia) about how the toilet flush works, gave judgments-of-learning (JOLs), were tested on the learning contents; afterwards this study-test cycle was repeated. Results from both experiments revealed stronger overconfidence due to multimedia in both study-test cycles (JOLs higher than learning outcomes). Eye movement data showed a relative increase in attention on the picture versus text from cycle 1 to cycle 2; this relative increase in attention was related to better learning outcomes. Repeated studying and testing thus helped to reduce over-reliance on text processing in multimedia learning, fostering performance. Highlights: Multimedia effects were analyzed on a process- and outcome-level in two study-test cycles. Robust multimedia effects were found across two study-test cycles. Lower performance in test 1 predicted longer studying in cycle 2. Attention distribution between text and picture was more balanced in cycle 2 than in cycle 1. Relatively longer picture processing in cycle 2 predicted better learning outcomes.